School-based interventions TO Prevent Dating and Relationship Violence and Gender-Based Violence: STOP-DRV-GBV systematic review - GJ Melendez-Torres; Noreen Orr; Caroline Farmer; Naomi Shaw; Annah Chollet; Andrew J Rizzo; Fraizer Kiff; Emma Rigby; Ann Hagell; Sidnei R Priolo Filho; Bruce Taylor; Honor Young; et al. (NIHR Journals Library, 2024)
Background Schools have a duty of care to prevent violence between students but a significant amount of dating and relationship violence and gender-based violence occurs in schools. These are important public health issues with important longitudinal consequences for young people. Objectives To understand functioning and effectiveness of school-based interventions for the prevention of dating and relationship violence and gender-based violence. Review methods We undertook a mixed-methods systematic review to synthesise different types of evidence relating to school-based interventions for the prevention of dating and relationship violence and gender-based violence to understand if, how and in what ways these interventions are effective. We searched 21 databases and 2 trial registers and undertook forwards and backwards citation chasing, author contact and other supplementary search methods. Searches identified all literature published to June 2021. All screening was undertaken in duplicate and independently, and we quality appraised all included studies. Results We included 247 reports (68 outcome evaluations, 137 process evaluations). Synthesis of intervention components produced an intervention typology: single-component, curricular, multicomponent, and multilevel programmes. Synthesis of intervention theories suggested that interventions aiming to increase students' sense of school belonging and sense of safety in the school building could encourage increased learning of prosocial skills and increased prosocial peer norms, and so potentially reducing dating and relationship violence and gender-based violence. Synthesis of factors affecting delivery highlighted school organisation and leaders who believed in the importance of addressing dating and relationship violence/gender-based violence, along with time and resources to deliver the interventions. The ease with which the intervention could be delivered and modified was also important. Meta-analysis found stronger evidence for intervention effectiveness in reducing dating and relationship violence than for gender-based violence, with significant long-term impacts on dating and relationship violence victimisation and perpetration, and some evidence that interventions in high-income countries could be effective for reducing victimisation and perpetration of gender-based violence in the long-term. Impacts on knowledge and attitudes were primarily short-term. Network meta-analysis did not suggest superiority of any intervention type. Moderation evidence suggested interventions reduced dating and relationship violence perpetration in boys more than girls, but reduced gender-based violence perpetration more in girls. Metaregression by intervention component did not explain heterogeneity in effectiveness, but qualitative comparative analysis suggested that reducing perpetration was important to reducing victimisation, and that perpetration could be reduced via focus on interpersonal skills, guided practice and (for gender-based violence) implementation of social structural components. Limitations Despite an exhaustive search, trials may have been missed and risk of publication bias was high for several analyses. Conclusions This is the most comprehensive systematic review of school-based interventions for dating and relationship violence and gender-based violence to date. It is clear that the prevention of dating and relationship violence and gender-based violence in schools will require longer-term investment to show benefit. Future work Future research is needed to understand why intervention effectiveness appears stronger for dating and relationship violence than gender-based violence. Study registration The study is registered as PROSPERO CRD42020190463. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme (NIHR award ref: NIHR130144) and is published in full in Public Health Research; Vol. 12, No. 3. See the NIHR Funding and Awards website for further award information. Plain language summary Schools are places where dating and relationship violence and gender-based violence occur. Therefore, interventions conducted within schools are ideally placed to prevent and reduce dating and relationship violence and gender-based violence. We reviewed existing research on these interventions, exploring how they were expected to work, what factors affected their implementation in practice, how they had an impact on dating and relationship violence and gender-based violence, and what specific parts of the interventions were most effective and in what contexts. We defined what sort of evidence to include in the review, carried out a comprehensive search and found 247 reports on school-based interventions to prevent dating and relationship violence or gender-based violence, most of which were conducted in North America. Most interventions aimed to provide students with the knowledge, attitudes and skills needed to prevent perpetration and victimisation. They varied in complexity; some had one activity, others had multiple activities, some were integrated into the existing school curricula and others were complex in that they sought to change how schools as a whole respond to dating and relationship violence or gender-based violence. We theorised that complex interventions would bring about greater and more sustainable change, but this was not supported by our findings. The implementation of interventions was affected by factors such as school organisation and leaders who believed in the importance of addressing dating and relationship violence/gender-based violence, along with time and resources to deliver the interventions. The ease with which the intervention could be delivered and modified was also important. There was stronger evidence for intervention effectiveness in reducing dating and relationship violence than for gender-based violence, with significant long-term impacts on dating and relationship violence victimisation and perpetration. There was some evidence that interventions in high-income countries could be effective for reducing victimisation and perpetration of gender-based violence in the long-term. More complicated interventions were not more effective, and interventions tended to reduce dating and relationship violence perpetration in boys more than in girls. We have also been able to identify where there are gaps in available evidence, which may provide avenues for future research. Scientific summary Background and rationale This systematic review focused on dating and relationship violence (DRV) and gender-based violence (GBV). The long-term impacts of both for young people are numerous and, consequently, addressing them is a public health priority. Adolescence is a crucial stage for focusing on the prevention of DRV and GBV and schools are an ideal location for this, as this is where young people are socialised into gender norms and where significant amounts of DRV and GBV occurs. Schools also offer an opportunity to reach many young people who may not otherwise be accessible for intervention. Previous reviews have evaluated the effectiveness of interventions for DRV or GBV for adolescents but do not specifically focus on interventions in schools or analyse outcomes jointly. Aim and review questions We systematically searched for and synthesised the evidence for the following research questions (RQs): What are the theories of change and components of evaluated interventions? What factors affect the implementation of evaluated interventions? Are interventions effective and cost-effective in preventing DRV and GBV and reducing social inequalities in these outcomes? Based on the findings of RQs 1-3, what factors are important for joint effectiveness on DRV and GBV outcomes? What is the comparative effectiveness of different approaches to DRV and GBV prevention? What do the different sources of evidence suggest about intervention mechanisms and how these are contingent on context? Methods Inclusion criteria We included randomised controlled trials and process evaluations of school-based interventions for DRV and/or GBV for children between 5 and 18 years. DRV was defined as physical, sexual and emotional violence (including coercive control) in relationships between young people.